Building public trust in state-owned financial institutions: Digital transformation, integrity culture, and employee experience as foundations of socio-institutional resilience - Chandra Fitra Arifianto; Nurfadilla; Putri Kinayah Sujani (Journal of Socio-Cultural Sustainability and Resilience, 2026)
Background: Public trust is a key foundation for organizational sustainability, particularly for state-owned financial institutions, which carry both economic and social mandates and function as key actors in sustaining public confidence and social resilience within the communities they serve. Research integrating digital transformation, integrity culture, and employee experience to explain public trust remains limited, particularly in the context of state-owned financial institutions in Indonesia. This study examines the influence of digital transformation, integrity culture, and employee experience on public trust at pawnshops, as a reflection of institutional resilience amid social and technological change. Methods: This study uses a quantitative explanatory design. The population included all pawnshop employees, with saturated sampling yielding 182 eligible respondents. Data were collected via a structured five-point Likert survey and analyzed using multiple linear regression in SPSS. Findings: All independent variables showed a positive and statistically significant influence on public trust. The regression model demonstrated strong explanatory power (Adjusted R² of 0.605), indicating that approximately 60.5% of the variation in public trust can be explained by these three variables collectively. Individually, employee experience emerged as the most influential predictor, followed by integrity culture, and then digital transformation. Conclusion: This study concludes that public trust in state-owned financial institutions is not solely determined by financial performance or technological advancement but is significantly shaped by the organization's internal capabilities. These findings highlight employees as key internal actors who translate organizational systems and values into publicly observable service behaviors, contributing to the broader socio-institutional resilience that underpins sustained public trust in society. Novelty/Originality of this article: The novelty lies in the integration of digital transformation, integrity culture, and employee experience into a single empirical model to explain public trust, particularly in the specific context of state-owned financial institutions in developing countries and their role in sustaining institutional resilience.